(untitled) (Medicine Today, 2015)
Spontaneous bacterial peritonitis (SBP) is an infection of ascitic fluid occurring in the absence of a contiguous source of infection characterized by symptoms of fever, abdominal pain, rebound tenderness, encephalopathy. It may develope in hospitalized patients and mortality rate is significantly high. To determine the prevalence of SBP in chronic liver disease with ascites and to establish that SBP is the cause of higher mortality than non SBP, a prospective longitudinal study was carried out in patients attending in the inpatient Department of Gastroenterology of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorder Hospital(BIRDEM), Bangabandhu Sheikh Mujib Medical University(BSMMU), Dhaka Medical College Hospital(DMCH), Dhaka from March 2010 to September 2010. Among the 60 patients the most common age group was the 46-55 years. In physical finding below average body build was found in 48 (80.0%) cases. Malnutrition was found in 48(80.0%) cases. Per abdominal finding liver was not palpable in 54 (90.0%) cases. Shifting dullness was found in 59 (98.3%) cases. Fluid thrill was detected in 57 (95.0%) cases. It was found that SBP were developed in 11(18.3%) cases and remaining 49(81.7%) case were non SBP, which were higher than SBP. Organism of culture of ascitic fluid in SBP patients (n=11) were E. coli and Pseudomoas spp found in 2(18.2%) cases, the rest 6(54.5%) cases shows no growth. Among 11 SBP patients improvement occurred in 5(45.5%) cases and the rest 6(54.5%) cases died p value <.001. SBP is medical emergency, prompt management and prophylactic antibiotics are essential to reduce mortality. Medicine Today 2015 Vol.27(1): 15-19